The Story of the Prophet Musa with Father-in-Law, Fir’aun, and Khidir: Psycghological Well Being Welfare Perspektif - Navi Agustina; Waharjani (PT. Nawa Edukasi Nusantara, 2026)
Psychological well-being is a concept that assesses a person's quality of life based on self-acceptance, purpose in life, positive relationships with others, independence, environmental mastery, and personal growth. In this study, the researcher examines the story of the Prophet Moses in three life stages that significantly shaped his psychological well-being: his relationship with his in-laws, his prophetic mission to confront Pharaoh, and his spiritual-cognitive learning process with the Prophet Khidir. This article analyzes how these three major experiences shaped Moses' psychological competence based on Carol Ryff's Psychological Well-Being theoretical framework. Furthermore, this study was also analyzed using classical and contemporary interpretation approaches. The results show that the Prophet Moses possessed all aspects of psychological well-being, but the strongest was the aspect of Life Purpose, followed by Self-Growth, Autonomy, Environmental Mastery, Self-Acceptance, and positive relationships with others. The Prophet Moses' psychological well-being occurred gradually, where his psychological well-being was supported by religiosity and social support, namely family. With the capital of his psychological well-being, Moses managed to overcome the difficult times he faced and succeeded in becoming a strong leader and defender of the oppressed.